A propósito del Covid-19. El rol de la edad y género en la inmunidad - González Campos, Óscar (Revista Hospital Clínico Universidad de Chile, 2020)
The purpose of the immune system is to protect the body from pathogenic microorganismssuch as bacteria, viruses, fungi and even tumor cells, which could cause disease. When theencounter with pathogens occurs, defenses are produced immediately through the innateresponse, faster and more nonspecific, and through the adaptive response, more defined andpersonalized for each attacker. Both are triggered by the cells of the immune system beingable to communicate with each other, once they have been activated. The innate immunesystem works in tune with the acquired immune system through the close intervention of thesex hormones, with specific strategies of estrogen and progesterone. Both have a provenanti-inflammatory and antioxidant action not only at the level of the wall of blood vessels, skinand mucous membranes, but also in the protection of the central nervous system against alltoxic agents, such as viruses. Estrogens and progesterone play an essential role in the immuneresponse and its evolution, and although they initially appear as antagonistic responses, theyare not, despite the fact that estrogens increase and progesterone seems to suppress theimmune response, depending on the immune target according to the case.